A Comparison of the LATCH Scores between Groups of Breastfeeding Women Using and Not Using a Nursing Pillow: A randomized, controlled trial - Sirikijkhajor, Supakit; Suksamarnwong , Maysita (Thai Journal of Obstetrics and Gynaecology, 2023)
Objectives: To investigate if the U-shaped nursing pillow can improve the LATCH scores in the postpartum breastfeeding mothers. Materials and Methods: Postpartum women who had an uncomplicated vaginal delivery and intended to breastfeed were eligible. Mothers who had no contraindications to breastfeeding were randomized into two groups: the nursing-pillow intervention group and the control group. All participants underwent breastfeeding education and training regarding the proper body position. They used a modified cradle technique 2-4 hours postpartum under the guidance of a well-trained breastfeeding nurse. The mothers in the intervention group were instructed to use the U-shaped nursing pillow, size 60 x 60 cm, with 25 - 30 cm thickness during every breastfeeding while they were in the maternity ward. The LATCH scores were assessed at 48 hours postpartum. The primary outcome was a mean difference in the LATCH scores between the groups. Results: A total of 48 eligible mothers were randomized into two groups: 24 in the nursing-pillow intervention group and 24 in the control group. The LATCH scores of the women who used a nursing pillow were significantly higher. The mean difference was 0.48 (95% confidence interval 0.06-0.90, p = 0.027). Conclusion: The groups of breastfeeding women using the U-shaped nursing pillow had higher LATCH scores than the control group.